Evaluation the combined diagnostic value of TAT, PIC, tPAIC, and sTM in disseminated intravascular coagulation: A multi-center prospective observational study. Issue 173 (January 2019) - Mei, Heng; Jiang, Ying; Luo, Lili; Huang, Ruibin; Su, Lei; Hou, Ming; Wang, Xuefeng; Deng, Jun; Hu, Yu
Abstract: Background: Accurate and early diagnosis is important in the management of disseminated intravascular coagulation (DIC). We employed new automation technology to detect plasma biomarkers, including thrombin-antithrombin complex (TAT), α2-plasmininhibitor-plasmin complex (PIC), soluble thrombomodulin (sTM), and tissue plasminogen activator-inhibitor complex (tPAIC), and evaluated their diagnostic performance and prognostic value for DIC in Chinese population. Methods: This prospective observational study included 444 patients with suspected DIC and 137 healthy people. The molecular markers were measured by qualitative chemiluminescence enzyme immunoassay performed on HISCL automated analyzers. All patients with suspected DIC were followed for 7 days to screen for the development of overt-DIC and 28 days for mortality. Results: According to the International Society of Thrombosis and Haemostasis (ISTH) scoring system, 157 patients were diagnosed as overt-DIC and 36 were diagnosed as pre-DIC. All four biomarkers were significantly higher in DIC patients than in non-overt DIC patients; TAT, tPAIC, and sTM were significantly higher in pre-DIC patients than in non-overt DIC patients. Four molecular markers behaved differently among various underlying diseases. TAT, tPAIC, and sTM were also good predictors of 28-day mortality, high levels were associated with poor outcomes. Conclusions: TAT, PIC, tPAIC, and sTM demonstrated good diagnostic performance and prognostic value in DIC patients with different underlying diseases. Besides, TAT, tPAIC and sTM have certain implications in pre-DIC stage. Combination of four makers was demonstrated better behavior than single one. Highlights: TAT, tPAIC and sTM have certain implication in pre-DIC stage. TAT, PIC, tPAIC and sTM demonstrated good diagnostic performance and prognostic value in DIC. Combination of four makers demonstrated better behavior than single one.